Hospital-dia: para quem e para quê? - Lima, Maria Cristina Pereira [UNESP]; Botega, Neury José (Associação Brasileira de Psiquiatria - ABP, 2001)
OBJETIVO: Estudar prospectivamente a população internada em um hospital-dia (HD) em relação a fatores que poderiam influenciar na melhora e na duração da internação. MÉTODOS: Foram entrevistados, para obtenção de dados sociodemográficos e avaliação da evolução, 34 pacientes internados no Hospital-Dia da Faculdade de Medicina de Botucatu, Unesp, durante um ano. O diagnóstico psiquiátrico foi avaliado pela CIDI (Composite International Diagnostic Interview), a sintomatologia psiquiátrica pela BPRS (Brief Psychiatric Rating Scale) e a incapacitação psicossocial pela DAS (Psychiatric Disability Assessment Schedule). Todos os pacientes foram acompanhados, e seus familiares, entrevistados. RESULTADOS: Predominaram mulheres (76%), jovens (61,8%), sem vínculo conjugal (71%), sem trabalho (82,4%), com diagnóstico de transtornos afetivos (44,1%) e com internações psiquiátricas prévias (44%). Apenas quatro (12%) pacientes apresentavam uma síndrome maior segundo BPRS. Houve considerável incapacitação psicossocial dos pacientes em alguns papéis sociais. Maior renda per capita foi um fator associado à melhor evolução. As internações duraram em média 74 dias. Pacientes com internações prévias tenderam a permanecer menos tempo no HD. CONCLUSÕES: Portadores de transtornos afetivos e quadros não-psicóticos geralmente não necessitam de internação por período integral em hospital psiquiátrico. Contudo, os pacientes deste estudo tiveram um elevado número de internações psiquiátricas prévias, provavelmente por necessitarem de um nível de atendimento além das possibilidades dos ambulatórios. Entretanto, pacientes com maior número de internações -- em tese mais graves -- tenderam a permanecer menos tempo no HD, o que suscita dúvidas quanto à sua adesão a serviços abertos, bem como aos possíveis fatores facilitadores dessa adesão. em um momento de crescimento expressivo no número de serviços de internação parcial no Brasil, como nos últimos anos, mais estudos são necessários a fim de esclarecer para quem e para quê são destinados esses serviços.

OBJECTIVE: To investigate prospectively factors that might have an impact on the outcome of psychiatric patients treated at a day-hospital. METHODS: Thirty-four patients admitted to the day-hospital of Botucatu Medical School -- UNESP during a period of one year were interviewed and their sociodemographic data and their clinical course were assessed. Psychiatric diagnoses were reviewed using the Composite International Diagnostic Interview, the psychiatric symptomatology was assessed using the Brief Psychiatric Rating Scale (BPRS) and the psychosocial incapacitation was evaluated using the Psychiatric Disability Assessment Schedule (DAS). All patients were followed up during the study period and their relatives were also interviewed. RESULTS: Most patients were women (76%), young (61,8%), not married (71%), unemployed (82.4%), diagnosed as having an affective disorder (44.1%), and with previous psychiatric hospitalizations (44%). Only 4 patients (12%) presented a major syndrome according to BPRS. However, patients showed substantial incapacitation regarding social functioning. Higher income was associated with better treatment outcome. Hospitalizations lasted 74 days on average. Patients who had been previously hospitalized had a shorter stay in the day-hospital. CONCLUSIONS: Patients with affective disorders and non-psychotic symptoms generally do not need in-patient care in a psychiatric hospital. However, the studied patients had had many previous psychiatric admissions, probably because they needed a more intensive treatment than outpatient services can offer. on the other hand, those patients who had had many previous hospitalizations (probably the most severe cases) remained for shorter periods of time in the day-hospital, which requires an examination of these patients' compliance with outpatient treatment as well as the factors influencing treatment compliance. Since there has been an expressive growth in the number of day-care services in Brazil in the last years, there is a need of further studies to determine these services' benefits and who can benefit from them.
Day hospital: for whom and for what?
Keywords: Hospital-dia; Transtornos mentais; Saúde mental; Política de saúde; Day hospital; Mental disorders; Mental health; Health policy